1998
DOI: 10.1080/09540129850124497
|View full text |Cite
|
Sign up to set email alerts
|

Survey of food safety awareness among HIV-positive individuals

Abstract: A survey was carried out by personal interview to assess the awareness of basic food hygiene and food safety amongst 77 HIV-positive individuals attending a single hospital. There was some confusion and lack of knowledge about aspects of food storage and despite the fact that 74% of subjects had modified their diet since learning their HIV status (mainly for nutritional reasons) only 25% reported receiving information on food safety. Of the subjects interviewed 96%, 66% and 23% were aware of the risks of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Among the food safety objectives are to increase the proportion of consumers who follow key food safety practices and to reduce foodborne infections caused by Salmonella , Campylobacter , Yersinia , and Vibrio species, Shiga toxin-producing Escherichia coli O157, and Listeria monocytogenes . Greater attention is needed to this basic health issue since AIDS patients are a highly vulnerable population for foodborne disease due to their immunocompromised condition, their lack of food safety knowledge [16,24], and their higher risk for morbidity and mortality [57]. Food safety educational materials should be more broadly available and incorporated into prevention counseling of AIDS patients along with other routine prevention messages such as those directed at immunization, medication adherence, and avoidance of STDs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the food safety objectives are to increase the proportion of consumers who follow key food safety practices and to reduce foodborne infections caused by Salmonella , Campylobacter , Yersinia , and Vibrio species, Shiga toxin-producing Escherichia coli O157, and Listeria monocytogenes . Greater attention is needed to this basic health issue since AIDS patients are a highly vulnerable population for foodborne disease due to their immunocompromised condition, their lack of food safety knowledge [16,24], and their higher risk for morbidity and mortality [57]. Food safety educational materials should be more broadly available and incorporated into prevention counseling of AIDS patients along with other routine prevention messages such as those directed at immunization, medication adherence, and avoidance of STDs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study has demonstrated a high consumption (40%) of bottled water by human immunodeficiency virus-positive patients (2). To date, there have been relatively few reports employing the use of molecular identification methods, particularly the use of rRNA identification techniques, to identify contaminating bacterial and fungal agents in bottled water.…”
mentioning
confidence: 99%
“…What few studies exist deal primarily with surveys of self-reported knowledge of food safety measures and hand-washing. Studies have shown that PLHIV lack knowledge of food safety measures [90]. In Ghana, Wiig and Smith [79] (2007) found that only 22 % of PLHIV boiled their water and only 66 % always reheated leftovers.…”
Section: Food Safetymentioning
confidence: 99%
“…Heathcock's [90] (1998) self-developed survey of 77 HIVpositive people in a hospitalized UK-based population showed that 96, 66, and 23 % were aware of the risk of infection from Salmonella, Listeria, and Cryptosporidium, respectively, but few were aware of infections transmitted through water. Program evaluation studies in the US have found home-delivered meal programs for PLHIV to be strongly adherent to food safety guidelines and have evaluated the effectiveness of educational tools [91].…”
Section: Food Safetymentioning
confidence: 99%